Production of antibodies to the constant region of the mouse T-cell-receptor β-chain - Schenkel, Johannes; Schäfer, Hubert; Koch, Susanne; Burger, Reinhard (Acta pathologica, microbiologica et immunologica Scandinavica, 1991)
To generate antibodies to the constant region of the mouse T-cell-receptor β chain, the corresponding cDNA clone 86T5 was subcloned into the bacterial expression vector pEX2. The induced hybrid protein consisting of a 30 kDa T-cell-receptor segment and a β-galactosidase carrier moiety was used for immunization. In Western blots using lysates of a T-cell-receptor-positive T-cell hybrid, the antisera obtained reacted with a 42 kDa protein under reducing and a 85 kDa protein under nonreducing conditions. The antisera did not react in binding assays with intact T lymphocytes, i.e. membrane-associated T-cell-receptor protein.